Ability to Early Identify Children with Special Needs with Barriers to Interaction, Communication and Behavior or Autism by Teachers at SLBN Tasikmalaya - Maharaeni, Amalia; Susetyo, Budi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The aim of this research is to see the ability of special education teachers in early identification of children with special needs. The early identification ability in question is for children with special needs with barriers to interaction, communication and behavior or autism. Research was conducted on SLB teachers at SLBN Tasikmalaya. The sample in the study used random sampling and collected 56 teachers as respondents. The data collection method uses a questionnaire with the option of using a Likert scale. Data were analyzed using descriptive quantitative in the form of percentages. The research results show that the teacher's ability to identify children with special needs is quite high. The results of the analysis show that its ability is in the high category at 70%. The distribution of other results is in the low category at 24% and the medium category at 6%. This high level of teacher ability is a good first step in preparing learning that is appropriate to the child's abilities so that the learning process and learning objectives can be achieved.